Hematology of the keeled box turtle (Cuora mouhotii). (1st May 2020) - Cerreta, Anthony J.; Houck, Emma L.; Stowe, Devorah M.; Lewbart, Gregory A.
Abstract: A healthy adult, intact female keeled box turtle ( Cuora mouhotii ) was found to have a marked heterophilic leukocytosis using normal hematologic parameters established for the eastern box turtle ( Terrapene carolina carolina ), a related chelonian species. This animal was monitored with serial complete blood counts (CBCs) over the next 15 years despite remaining asymptomatic for an infectious condition. Retrospective CBC data were compiled from 38 presumably healthy keeled box turtles to establish hematologic values for comparison in this species. Using this species‐specific data, over the 15‐year period, the female keeled box turtle had two times where the white blood cell (WBC) count was greater than 2 standard deviations (SD) above the mean, six times where the WBC count was greater than 1 SD above the mean, six times where the PCV was greater than 2 SD above the mean, and eight times where the PCV was greater than 1 SD above the mean. Infection and inflammation are the most common causes of leukocytosis in reptiles; however, given the clinical presentation of this patient, it was postulated that these clinicopathologic changes could be secondary to a stress response. Establishing reference intervals and understanding how stress impacts CBC parameters are important for evaluating the health status of keeled box turtles kept in captivity and for assessing the effects of environmental changes on the health status of wild populations of this endangered chelonian species.